The "molten sea", or is it? - Kang, Seung Il (Biblica, 2008)
Contrary to the conventional rendering hay-yām mûṣāq (1 Kgs 7,23), the name of the huge water basin in the Solomonic Temple, as the "Molten Sea", the author suggests that hay-yām mûṣāq should be seen as one of the cultic proclamations declared during the New Year festival and should be translated "The Sea has been constrained!"